2013
DOI: 10.1007/s12039-013-0463-1
|View full text |Cite
|
Sign up to set email alerts
|

Binding of reactive organophosphate by oximes via hydrogen bond

Abstract: In this contribution, the ability of simple oximes to bind a well-known nerve agent simulant (dimethylmethylphosphonate, DMMP) via hydrogen bond is reported. UV/Vis measurements indicate the formation of 1:1 complexes. 1 H-, 31 P-NMR titrations and T-ROESY experiments confirm that oximes bind the organophosphate via hydrogen bond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…Our research group studied three different oximes (Figure 5A) having the ability to interact with DMMP in solution through the formation of hydrogen bond [50] . This ability was investigated by NMR and UV‐Vis spectroscopy.…”
Section: Sensing By Supramolecular Approachmentioning
confidence: 99%
“…Our research group studied three different oximes (Figure 5A) having the ability to interact with DMMP in solution through the formation of hydrogen bond [50] . This ability was investigated by NMR and UV‐Vis spectroscopy.…”
Section: Sensing By Supramolecular Approachmentioning
confidence: 99%
“…For example, DMMP contains phosphoryl (P=O) groups, that give stronger hydrogen bonds to any available surface. (91) On the GO surface, oxygen functional and modified functional groups are available to form hydrogen bonds with DMMP. A study of the chemical interaction of DMMP and a self-assembled interface by Bertilsson et al showed that an acid surface (−COOH) has the strongest DMMP adsorption.…”
Section: Detection Of Chemical Warfare Agent Simulantmentioning
confidence: 99%
“…Reactions of oximates with OP CWAs and their simulants are well-known, 8,2427 and the parent oxime (4-nitrobenzaldoxime) is known to react with DCP and undergo a Beckman rearrangement to yield 4-nitrobenzonitrile. Confirmation of the reaction of 6 with DCP, and potentially DMMP, was sought in DMSO- d 6 in the presence of 5 , which does not form an organogel and thus removes additional complexities of studying reactions within organogel substrates.…”
Section: Synthesismentioning
confidence: 99%